Rapid and Accurate Diagnosis of Pediatric Tuberculosis Disease: A Diagnostic Accuracy Study for Pediatric Tuberculosis. Issue 5 (16th February 2023) - Olbrich, Laura; Nliwasa, Marriott; Sabi, Issa; Ntinginya, Nyanda E.; Khosa, Celso; Banze, Denise; Corbett, Elizabeth L.; Semphere, Robina; Verghese, Valsan P.; Michael, Joy Sarojini; Graham, Stephen M.; Egere, Uzochukwu; et al.
Abstract : Introduction: An estimated 1.2 million children develop tuberculosis (TB) every year with 240, 000 dying because of missed diagnosis. Existing tools suffer from lack of accuracy and are often unavailable. Here, we describe the scientific and clinical methodology applied in RaPaed-TB, a diagnostic accuracy study. Methods: This prospective diagnostic accuracy study evaluating several candidate tests for TB was set out to recruit 1000 children <15 years with presumptive TB in 5 countries (Malawi, Mozambique, South Africa, Tanzania, India). Assessments at baseline included documentation of TB signs and symptoms, TB history, radiography, tuberculin skin test, HIV testing and spirometry. Respiratory samples for reference standard testing (culture, Xpert Ultra) included sputum (induced/spontaneous) or gastric aspirate, and nasopharyngeal aspirate (if <5 years). For novel tests, blood, urine and stool were collected. All participants were followed up at months 1 and 3, and month 6 if on TB treatment or unwell. The primary endpoint followed NIH-consensus statements on categorization of TB disease status for each participant. The study was approved by the sponsor's and all relevant local ethics committees. Discussion: As a diagnostic accuracy study for a disease with an imperfect reference standard, Rapid and Accurate Diagnosis of Pediatric Tuberculosis Disease (RaPaed-TB) was designed following a rigorous and complex methodology. This allows for the determination of diagnostic accuracy of novel assays and combination of testing strategies for optimal care for children, including high-risk groups (ie, very young, malnourished, children living with HIV). Being one of the largest of its kind, RaPaed-TB will inform the development of improved diagnostic approaches to increase case detection in pediatric TB.